The Influence of Internal Control, Organizational Commitment, and Rule Compliance on Accounting Fraud Tendencies - Gunawan Barbara; Rizoan Nabiilah Taqiyyah (SHS Web of Conferences)
This study examines the effect of internal control, organizational commitment, and rule compliance on accounting fraud tendencies. The sample used is the Local Government Organization (OPD) employees of Musi Rawas Regency using purposive sampling techniques. With respondent criteria, Commitment Officers, Financial Administration Officers, Expenditure/Revenue Treasurers (for OPDs where there is a revenue treasurer), Assistant Treasurers, and Finance Staff at Local Government Organizations. This study used primary data, namely in the form of responses from respondents obtained through the distribution of questionnaires. This research tested the relationship between variables quantitatively with Partial Least Squares-Structural Equation Modeling (PLS-SEM) using the SmartPLS v.4. The research results show that internal control does not affect accounting fraud tendencies. At the same time, organizational commitment and rule compliance have a negative effect on accounting fraud tendencies.